Alice Deignan, Jeannette Littlemore, Elena Semino (2013). Figurative Language, Genre and Register - Imamović, Adisa (ExELL, 2013)
This is a review of:Alice Deignan, Jeannette Littlemore, Elena Semino (2013). Figurative Language, Genre and Register.